Evaluation of energy efficiency for Residential New Construction (RNC) single storey terrace house - Anuar , Mohamed Kassim; Jamri , Mohd Saifuzam; Othman, Md Nazri; Jaafar, Hazriq Izzuan (2014)
The impermanence changing of the climates that cause many natural disasters these days has raised the attention of us about the importance of greening towards our planet. The building sector has been verified as the major part of the global solutions. Hence, Green Rating Tools are recommended internationally to guide the developers and public in designing and developing green buildings in order to reduce the negative impact towards human health and environment due to increasing use of natural resources. The research on energy efficiency of Residential New Construction (RNC) was successfully done and analyzed by using the DIALux software and light illumination calculations.